Aiming at the tumor-specific accumulation of MGMT-inhibitors: First description of a synthetic strategy towards inhibitor-peptide conjugates - Wängler, Björn; Schirrmacher, Ralf; Wängler, Carmen (Tetrahedron letters, 2020)
In the therapy of cancer, alkylating agents are an efficient and often-used substance class. However, cells can repair the resulting alkyl modifications in the O-6-position of guanine using the repair protein methylguanine methyltransferase (MGMT), giving rise to resistance and inefficient therapy. A possibility to overcome this resistance is the use of MGMT inhibitors as adjuvants to alkylating therapies. However, MGMT inhibitors also sensitize healthy cells towards alkylating therapies. A strategy to circumvent this is the development of tumor-specific inhibitors which could be based on peptidic ligands as carriers. Such constructs would enable a receptor-specific uptake into tumors. Furthermore, the MGMT inhibitors could be adapted to the respective tumor entity by changing the peptide carrier. However, no peptide-based tumor-specific MGMT inhibitors were described so far. Thus, we have developed a synthetic strategy to obtain covalent conjugates of receptor-specific peptides and O-6-benzylguanine derivatives. As model compounds, the MGMT inhibitor O-6-(3-bromobenzyl)guanine and the receptor-specific peptides c (RGDfK), TATE, PESIN, neurotensin-2656 and minigastrin-9 were chosen and successfully assembled to obtain potentially tumor-specific MGMT inhibitors. Both, the O-6-(3-bromobenzyl)guanine as well as the peptide derivatives are easily replaceable during the syntheses to tailor peptide-based bioconjugates adaptable to the specific tumor entity. (C) 2020 Elsevier Ltd. All rights reserved.